Clients Satisfactions In ISO Certified Health Clinic In Klinik Kesihatan Bandar Baru Bangi, Selangor And Its Associated Factors - Aniza I,; Suhaila A, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2011)
Background : All healthcare services are moving towards quality management system including ISO 9000 due to pressure from various stakeholders involves and also to improve healthcare quality. The objective of this study was to measure the satisfaction level among the outpatients in ISO Certified Klinik Kesihatan Bandar Baru Bangi, Selangor. Also to identify the relations of patient’s satisfaction with the sociodemographic factors and service dimensions such as general satisfactions, technical quality of clinic staffs, interpersonal aspect of clinic staffs, time with doctors, communications with clinic staffs and availability/accessibility of clinic. Methodology : A cross sectional study was carried out from February 2008 to Jun 2008 and a total of 240 respondents in the clinic were selected using universal sampling. Only those who are Malaysians aged 18 and above and complied with the inclusions criteria’s were selected as the respondents to fill up the Patient’s Satisfaction Questionnaire III. Result : The study found that the satisfaction level of the respondents in Klinik Kesihatan Bandar Baru Bangi, Selangor were remarkable with 78.8%.It has been shown that the predictor factors of total patient’s satisfaction were general satisfaction (AOR=5.06, CI= 1.51-16.96), technical quality of clinic staff (AOR = 3.09, CI= 1.13-8.43), interpersonal aspect of clinic staff (AOR = 2.96,CI= 1.04-8.42), availability/accessibility of clinic (AOR = 9.38, CI= 9.37-87.95) and communication of clinic staff ( AOR=17.90, CI=3.74-85.73) with the R2 = 67.7%. Conclusion : The satisfaction level among the respondents in Klinik Kesihatan Bandar Baru Bangi, Selangor were remarkable with percentages of 78.8%. The study has shown that service dimensions factor influenced the patient’s satisfaction such as general satisfaction, interpersonal aspect of staff, communication of staff, technical quality of clinic staff and availability/accessibility of clinic. It could have also been contributed by the implementation of ISO and it can only be confirmed by carrying out a comparison study of patient’s satisfaction in clinics with and without ISO certification.